The growth performance and prospects in Europe: A Kaldorian approach - Carluccio Bianchi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2004)
This paper purports to apply the balance of payments constrainedgrowth model to explain the European growth performance in the last forty years and to discuss the likely prospects for the future. After a formal reconsideration of the long-run and short-run arguments supporting the validity of the Post-Keynesian approach to economic growth, a simplified and an extended version of the basic model are outlined. The application of the model to the European experience shows that the so-called Thirlwall's law performs quite well in explaining facts in all the decades under consideration. The fundamental reasons behind the unsatisfactory recent EU growth experience lie therefore in a decreasing (absolutely and relatively to other advanced countries) exports dynamics and in an increasing imports dependence. On the basis of the existing trends, the prospects for the future appear to be gloomy, unless structural reforms of the productive system are promoted in order to improve the position of Europe in the international division of labour.
Keywords: O40; O52; 330; Growth; Europe; Thirlwall's law; Wachstumstheorie; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; Postkeynesianismus; EU-Staaten